Comparative evaluation of parametric design systems for teaching design computation. (September 2017) - Aish, Robert; Hanna, Sean
Abstract : Three parametric design systems were tested by the authors to assess their suitability for undergraduate teaching. We used criteria taken from the 'cognitive dimensions' literature and an exercise of typical geometric operations in ascending order of complexity. For each system the cognitive barriers associated with the sequence of operations were plotted to create a 'learning curve'. Different parametric systems presented distinctly different learning curves. The test exercise had to be completed in its entirety to assess the potential challenges which students with different educational levels, skills and abilities might encounter, so a single expert user conducted the tests. This research is intended to develop methods, both design exercises and evaluative criteria that could be used in future empirical studies. Highlights: How parametric systems support parametric design thinking is of critical importance. The cognitive challenges presented by parametric systems were evaluated. From this evaluation the cognitive challenges are described by learning curves. Different parametric design systems present distinctly different learning curves.